Week-to-week variations of internal and external intensity measures in professional women volleyball players - Lima, R.; Gracinda, A.; Silva, B.; Silva, A. F.; Pereira, J.; Silva, R. M.; Clemente, F. M. (International Journal of Sports Science & Coaching, 2024)
The aim of the present study was twofold: (i) to analyze the relationship between weekly variations in ACWR, training monotony (TM), training strain (TS), s-RPE and the number of jumps; and (ii) to explore the association between tests based on the external and internal training intensity (TI) measures across weeks. An observational cohort study was conducted. Ten female elite volleyball players (two setters, three middle-blockers, three outside hitters, and two opposites) of a first Division Portuguese team (24.1 ± 6.12 years old; 66.48 ± 6.85 kg; and 175.4 ± 6.52 cm) participated in this study. Players were monitored for external and internal TI measures. The correlation coefficients between internal and external TI measures were determined using Pearson's r. The results showed a moderate relationship between weekly variations of ACWR, TM, TS, s-RPE, and the number of jumps. Additionally, a moderate association between external and internal TI measures were detected. In conclusion, s-RPE seems to be a more sensible measure than the number of jumps, since its percentage of variation was higher.